Homely atmospheres and lighting technologies in Denmark - Bille, Mikkel, author.
1 online resource (192 pages)
Keywords: Using case studies, such as the use of candlelight and energy saving lightbulbs in Denmark, this book unravels light's place at the heart of social life. In contrast to common perception of light as a technical and aesthetic phenomenon, Mikkel Bille argues that there is a cultural and social logic to lighting practices. By empirically investigating the social role of lighting in people's everyday lives, Mikkel Bille reveals how and why people visually shape their homes. Moving beyond the impact of its use, Bille also comments on the politics of lighting to examine how ideas of pollution and home act as barriers for technological fixes to curb energy demand. Attitudes to these issues are reflective of how human perceptions and practices are central to the efforts to cope with climate change. This ethnographic study is a must-read for students of anthropology, cultural studies, human geography, sociology and design.